Universal Access to Two‐Dimensional Mesoporous Heterostructures by Micelle‐Directed Interfacial Assembly. Issue 44 (26th August 2020) - Wang, Jie; Chang, Zhi; Ding, Bing; Li, Tao; Yang, Gaoliang; Pang, Zhibin; Nakato, Teruyuki; Eguchi, Miharu; Kang, Yong‐Mook; Na, Jongbeom; Guan, Bu Yuan; Yamauchi, Yusuke
Abstract: Two‐dimensional (2D) mesoporous heterostructures combining ultrathin nanosheet morphology, periodic porous surface structures, and diverse hybrid compositions have become increasingly important for renewable energy storage and electronics. However, it remains a great challenge to develop a universal method to prepare 2D mesoporous heterostructures. Herein, we report a composite‐micelle‐directed interfacial assembly method to synthesize heterostructures of an ultrathin 2D material covered with mesoporous monolayers assembled on both sides. To demonstrate the concept, we first fabricated a new sandwichlike carbon@MXene@carbon mesoporous heterostructure through the self‐assembly of exfoliated MXene nanosheets and block copolymer F127/melamine‐formaldehyde resin composite micelles and subsequent thermal treatment. Finally, we demonstrate that the carbon@MXene@carbon mesoporous heterostructured nanosheets manifest remarkably enhanced electrochemical performance as a cathode material for lithium–sulfur batteries. Abstract : A general composite‐micelle‐directed interfacial assembly method was developed to prepare mesoporous heterostructures (see picture). With their structural and compositional advantages, the unique sandwichlike mesoporous carbon@MXene@mesoporous carbon heterostructured nanosheets exhibited remarkable electrochemical performance as a cathode material for lithium–sulfur batteries.